Piracy around the Horn of Africa - Joshua Ho (EchoGéo)
Piracy around the Horn of Africa has risen to a level serious enough for the international community to take concerted action to secure an international sea lane. However, the efforts so far have been initiated mainly by the international community while regional efforts are only just beginning. In the short term, more action will have to be taken at the operational level like dispatching more ships and integrating the operations of ships already deployed to the area. In the longer term, the root causes of piracy and the grievances of the Somali people have to be addressed. In particular, there is a need to restore law and order in Somalia by supporting moderate leaders in their attempts to create a representative government.